”We can’t just do it any which way” – Objectivity Work among Swedish Prosecutors - Jacobsson, Katarina (Qualitative Sociology Review, 2008)
Objectivity is a principle widely acknowledged and honoured in contemporary society. Rather than treating objectivity as an a priori defined category to be tested empirically, I refer to the construction of objectivity as it is accomplished in practice as “objectivity work” and consider how Swedish prosecutors in interviews make and communicatively realize (i.e. “make real”) its claims. In analyzing two facets of objectivity work – maintaining objectivity and responses to objectivity violations – seven mechanisms are identified: appeals to (1) regulation, (2) duty, and (3) professionalism; responses to violations by (4) incantations of objectivity, (5) corrections, (6) proclamation by contrast, and (7) appeals to human fallibility. Directions for future research emphasize cross-cultural and crossoccupational comparisons, not only within the judiciary as objectivity is of a general concern in any area where disinterested truths are claimed. The concept of objectivity work allows one to study how various actors bring principle into everyday life.